Feeding Ecology and Diet Composition of Rhesus Macaques (macaca Mulatta Ssp. Mulatta) in Chitrakoot Region, India - Tomar, Sangeeta; Sikarwar, R. L. S. (Indian Forester, 2014)
A detailed study on the ecology and food selection of rhesus macaque (Macaca mulatta ssp. mulatta) in Chitrakoot area was carried out during the year 2009-2011. During the study, twenty five troops of rhesus macaques were found in temple, urban, roadside, riverside, forest habitats and near human settlements. They consume fruits, flowers, leaves, buds, seeds, etc of 104 plant species, some insects and 32 items of provisioned foods. The diet composition of rhesus macaques in Chitrakoot area is constituted with 67.11% from provisioned food items, 27.45% from plants and their parts and 5.45% from the insects.